Proposals for Second Five Year Plan Labour Department Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
The Plan schemes of the Labour Department are based on the fact that it has certain responsibilities towards labour in general which include agricultural, non-agricultural and industrial workers. In setting out the labour policy also, the Government of Madhya Bharat had stressed the following cardinal, points, viz., (1) agricultural labour to be given as much importance as the industrial labour, (2) standardization of wages in different industries and the fixation of regional minimum wages, (3) need for introducing uniform labour laws in all the Covenanting States, (4) creation of a machinery for the enforcement of the various labour laws, and (5) constitution of advisory boards, workers production and welfare committees.
Labour Department
Government of Madhya Bharat
Keywords: General Summary; Employment to be generated; Requirements of technical personnel and their recruitment programme; Central & State’s shore of expenditure; Financial commitments Involved and the targets envisaged in 1956-57; Labour Welfare Centres; Victimization (Trade Union) Benefit to dismissed workers; Technical & Vocational Training Centres; Research & Publicity Section; Maternity Wards